Implementation of a Knowledge Management System to Enhance Innovation and Collaboration in Higher Education - Muttaqi, Fajar; Alfaujianto, Moh. (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2026)
This research addresses the growing need for effective knowledge management in higher education to foster innovation and collaboration. It focuses on designing and implementing a Knowledge Management System (KMS) for universities using a hybrid method that combines Waterfall and Agile approaches. Data were collected through surveys, interviews, and observations with lecturers, students, and staff. The system, built with the MERN stack and integrated with AI and Big Data analytics, includes three main modules: a centralized knowledge repository, collaboration tools, and an AI-based recommendation engine. User testing showed positive results—82% satisfaction with usability, 76% improved collaboration, and 85% accurate recommendations. The KMS enhances knowledge sharing and innovation, with future work targeting scalability and predictive analytics.